2006
DOI: 10.1007/s11064-006-9088-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential Involvement of Intracellular Ca2+ in 1-Methyl-4-phenylpyridinium- or 6-Hydroxydopamine-Induced Cell Viability Loss in PC12 Cells

Abstract: 1-Methyl-4-phenylpyridinium (MPP(+)) or 6-hydroxydopamine (6-OHDA) caused a nuclear damage, the mitochondrial membrane permeability changes, leading to the cytochrome c release and caspase-3 activation, the formation of reactive oxygen species and the depletion of GSH in PC12 cells. Nicardipine (a calcium channel blocker), EGTA (an extracellular calcium chelator), BAPTA-AM (a cell permeable calcium chelator) and calmodulin antagonists (W-7 and calmidazolium) attenuated the MPP(+)-induced mitochondrial damage a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
3
10
0
Order By: Relevance
“…ROS act upon mitochondria, causing a disruption of mitochondrial membrane potential and the release of cytochrome c (Fleury et al, 2002). It has been shown that MPP + induces the formation of ROS and nitrogen species, which is involved in mitochondrial dysfunction and cell death (Lee et al, 2006(Lee et al, , 2007. Inhibitory effect of antioxidants such as N-acetylcysteine and carboxy-PTIO on the MPP + -induced activation of caspase-3 may support the results of the previous reports.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…ROS act upon mitochondria, causing a disruption of mitochondrial membrane potential and the release of cytochrome c (Fleury et al, 2002). It has been shown that MPP + induces the formation of ROS and nitrogen species, which is involved in mitochondrial dysfunction and cell death (Lee et al, 2006(Lee et al, , 2007. Inhibitory effect of antioxidants such as N-acetylcysteine and carboxy-PTIO on the MPP + -induced activation of caspase-3 may support the results of the previous reports.…”
Section: Discussionsupporting
confidence: 73%
“…PC12 cells upon the nerve growth factor stimulation not only display abundant neuritic growth, but also adopt a neurochemical dopaminergic phenotype (Kadota et al, 1996). The MPP + -induced apoptosis in neuronal cells is mediated by formation of the mitochondrial permeability transition, which results in the release of mitochondrial cytochrome c and subsequent activation of caspase-3 (Cassarino et al, 1999;Lee et al, 2006). In agreement with these reports, the MPP + induced cell death seems to be mediated by activation of caspase-3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several mechanisms including impaired mitochondrial complex-I activity, mitochondrial permeability transition pore (MTP) formation, increased expression of Fas and caspase activity have been reported in post-mortem brain samples of Parkinson's disease patients. [1][2][3][4][5][6][7] Moreover, in vitro studies also support a role of apoptosis in the neurotoxin induced death of neurons. 1-Methyl-4-phenylpyridinium (MPP + ) or 6-hydroxydopamine (6-OHDA) in a concentration-dependent manner increased cytochrome-c release into the cytosol, caspase's activity, uncoupling of mitochondrial oxidative phosphorylation and decreased mitochondrial membrane potential in human neuroblastoma SHSY5Y cells, PC12 cells, mesencephalic dopaminergic neurons and in MN9D dopaminergic neuronal cells has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In order to avoid the photo-oxidation of DCF, we used a single rapid scan to assemble the fluorescence images, and the same settings were used for all tests. (Lee et al, 2006;Yamamoto et al, 2007) …”
Section: Intracellular Ros Analysismentioning
confidence: 99%